Oil palm tree Crowns delineation and enumeration using satellite images - Chai, Soo See (Faculty of Computer Science and Information Technology, 2003)
Manual interpretation of medium and high spatial resolution aerial imagery for forestry has evolved during the 20th century. For this type of application, manual delineation and enumeration of the tree crowns on the aerial images are the main activities required. At late of that century, a new research branch which aims at fully of partly replace human image interpreter by a "seeing computer" was born.